Enhancing sharia financial literacy and digital governance to improve productivity of Saiyeg Saeko Proyo Cooperative Members - Mustofa; Muhammad Roestam Afandi; Nita Kusumawardani (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2026)
This community service program was conducted to enhance the productivity and sharia financial literacy of members of the Saiyeg Saeko Proyo Cooperative, who were found to have a limited understanding of sharia financial principles, financial planning, and cooperative institutional management. The objective of this activity is to improve the understanding, skills, and attitudes of cooperative members in managing finances and shaping business productivity, transparency, and consistent with sharia principles. The implementation methods including survey and analysis of partner needs, three days of intensive training, and continuous mentoring for six months. The approach used is participatory and implemented through interactive lectures, group discussions, case studies, practical simulations, and periodic evaluations. Attended by 35 cooperative members, the evaluation results showed 46.6 percent increase in the average sharia financial literacy score of all participants, from 56.4 in the pre-test to 82.7 in the post-test. Additionally, total of 77.1 percent or 27 participants was able to prepare simple financial records independently, while 82.9 percent or 29 participants began using a digital system for cooperative administration. The cooperative members demonstrated improved accountability in financial reporting and a willingness to establish new business units based on member needs. Therefore, this activity successfully strengthened both individual and institutional capacity within the cooperative and supported economic empowerment based on sharia principles.